Building spaces of dialogue: a proposal for teaching bioethics - Gómez Urrutia, Verónica; Royo Urrizola, Paulina (Acta Bioethica, 2015)
This article sustains, describes and evaluates a proposal for teaching bioethics which privileges the use of ethical dialogue as methodological framework. This favors the incorporation of the experience of students in the process of teaching-learning. This model was applied to 52 third year Medicine students of the University of Talca (Chile). They also evaluated the experience from the perspective of the personal resources who must be mobilized in order to fulfill the course with success, as well as the possible contexts to apply what have been learned. Facing the spread of superior education and the unpredictability of the new ethical challenges, due to the advancement of technology, the model contributes to the development of ethical autonomy of the students.